Nurses conduct in the treatment of wounds in an intensive care unit - Rosa Aparecida Nogueira Moreira; Terezinha Almeida Queiroz; Márcio Flávio Moura de Araújo; Thiago Moura de Araújo; Joselany Áfio Caetano (Rev Rene)
This is an exploratory study, whose data were collected during the months of January and February 2007 in an intensive care unit in Fortaleza-CE. The aim of the study was to check the conduct of nurses in a public hospital on the treatment of wounds. The data collection was given by the record of a structured form. All the nurses said to register the data and adopt a criterion for evaluation, specific to wounds. Regarding the assessment criteria it was emphasized: the presence of exudate (56.2%), the extent, depth and type of tissue, each with 43.7% of the answers. About 90% of the surveyed considered the work important in the multidisciplinary treatment of wounds. It was concluded that nurses are well aware of the therapeutic methods of looking after wounds.